2022
DOI: 10.3390/pharmaceutics14112422
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Loaded Oil-Free Self-Assembled Micelles Inhibit the Influenza A Virus Activity and the Solidification of Curcumin-Loaded Micelles for Pharmaceutical Applications

Abstract: Curcumin, a well-known natural lipophilic phenolic compound, plays a vital role in inhibiting the influenza infection. Currently, many kinds of formulations for the enhancement of a water dispersion of curcumin have been developed; however, the anti-influenza abilities of formulated curcumin have been much less investigated. In this study, the optimized self-assembled micelles of RH 40/Tween 80 loaded with curcumin (Cur-M) in an oil-free-based system were spherical with a hydrodynamic size at 13.55 nm ± 0.208 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Similar results were obtained in a previous study in which Kolliphor RH40 and Tween 80 were used as surfactants and cosurfactants to successfully prepare small micelle formulations. 52 The compositions and particle size analysis of empty micelles with small particle sizes (EM-S) and CM-S performed by the DLS method are summarized in Table 1 . As shown in Figure 4A2 and Table 1 , EM-S and CM-S showed small average diameters of 10.27±0.11 nm and 17.16±0.77 nm along with narrow polydispersity indices (PDIs) of 0.110±0.004 and 0.194±0.009, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in a previous study in which Kolliphor RH40 and Tween 80 were used as surfactants and cosurfactants to successfully prepare small micelle formulations. 52 The compositions and particle size analysis of empty micelles with small particle sizes (EM-S) and CM-S performed by the DLS method are summarized in Table 1 . As shown in Figure 4A2 and Table 1 , EM-S and CM-S showed small average diameters of 10.27±0.11 nm and 17.16±0.77 nm along with narrow polydispersity indices (PDIs) of 0.110±0.004 and 0.194±0.009, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Empty micelles (EMs) and CMs were prepared using a modified self-assembly technique. 52 Generally, Cur was dissolved in solvent (ethanol) at 60°C as the core phase. The shell phase consisting of surfactant or cosurfactant was then added to the core phase with violent stirring at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetic advantage of the use of nanoformulations was also highlighted in other in vitro studies, including one by Li et al [ 160 ]. In this research, curcumin-loaded self-assembled micelles demonstrated considerable benefits over the molecule in bulk form.…”
Section: Natural Products and Nanotechnological Approach To Treating ...mentioning
confidence: 86%